Evolution Mechanisms of Three-Dimensional Fracture Fields in Coal Under Uniaxial Cyclic Loading and Unloading - Jiankun Xu; Rui Zhou; Danyang Xi; Yichao Lin; Xibin Li (Applied Sciences)
In deep underground engineering applications, such as coal mining, coal–rock masses are frequently subjected to repeated loading and unloading conditions. Understanding the evolution mechanisms of their internal three-dimensional fracture fields has become a critical scientific challenge. This study utilized X-ray Microscopy (XRM) to observe changes in internal fractures of coal samples after each loading–unloading cycle, reconstructing the internal fractures and mineral particles. Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) were employed to analyze the surface morphology and mineral composition of coal sample cross-sections. The experimental results revealed that: (1) With an increasing number of loading–unloading cycles, the samples’ volumes initially decreased and then expanded, with the expansion accompanied by rapid propagation of CT-scale fractures; (2) During the linear elastic phase, micro-fractures developed progressively but remained small, while sustained stress caused these fractures to interconnect, eventually leading to macroscopic failure; (3) Hard mineral particles within the coal samples, such as iron ore, acted as barriers to crack propagation. These findings indicate that the evolution characteristics of the internal fracture fields in coal–rock masses are influenced by stress state, pre-existing fractures, and the distribution of mineral particles.